Implementation of ESG strategy when building brands in the Belarusian market - Liu , Haozhen; Duktava, Liubou G. (Journal of the Belarusian State University. Journalism, 2024)
The article discusses the experience of implementing ESG strategy of companies operating in the Belarusian market, aimed at solving environmental, social, and corporate governance problems. Among the main directions of the implemented ESG projects were ecology (measures aimed at reducing the impact on the environment through the use of energy-efficient systems for servicing communication networks and reducing the carbon footprint), inclusion, improving digital literacy, assistance to children, as well as support and development of national culture. It is argued that the implementation of the ESG initiative involves the use of media and GR technologies. Examples from the practice of Belarusian mobile operators «A1», «MTS» and institution «ASB Belarusbank» are considered.